In Vivo Inhibition of Porphyromonas gingivalis Growth and Prevention of Periodontitis With Quorum‐Sensing Inhibitors. Issue 9 (1st September 2016) - Cho, Young‐Jae; Song, Hyun Young; Ben Amara, Heithem; Choi, Bong‐Kyu; Eunju, Ryu; Cho, Young‐Ah; Seol, Yangjo; Lee, Yongmoo; Ku, Young; Rhyu, In‐Chul; Koo, Ki‐Tae
Abstract : Background: Autoinducer (AI)‐2 has an important role in biofilm formation in the oral environment. Mature biofilms formed as a result of the cell‐to‐cell communication make it difficult to overcome periodontitis with the use of antibiotics. Previous in vitro studies suggest that quorum‐sensing inhibitors (QSIs) interfere with AI‐2. This study compares the QSI effects resulting from an oral inoculation of Porphyromonas gingivalis in an experimental animal model. Methods: Forty‐five male mice were divided into three groups (n = 15 each): 1) infection; 2) QSI; and 3) control. Infection and QSI groups received oral inoculation of P. gingivalis, whereas treatment with QSIs (furane compound andd ‐ribose) was only performed in the QSIs group. The control group was a negative control not receiving manipulation. After 42 days, mice were sacrificed, and the distance from the alveolar bone crest (ABC) to the cemento‐enamel junction (CEJ) was measured by microcomputed tomography. P. gingivalis DNA was quantified in the soft and hard tissues around the molar teeth by real‐time polymerase chain reaction. Results: Distance from ABC to CEJ was significantly increased in the P. gingivalis infection group compared with the control group ( P = 0.02) and significantly decreased in the QSI group compared with the infection group ( P = 0.02). The QSI group contained 31.64% of the bacterial DNA count of the infection group. Conclusion: Use of QSIs in the mice infection model showed a reduction of bone breakdown and a decrease in the number of bacteria in vivo, suggesting that QSIs can be a new approach to prevention and treatment of periodontitis.